Palatable Sharia: Killing Two Birds with One Stone - Ikhwan, Hakimul (Al-Jamiah Research Centre, 2018)
Based on observation in the District of Cianjur, West Java, Indonesia shariatization was a form of local re-packaging sharia where the term âshariaâ has been replaced with âAkhlaq al-Karimahâ (noble character). It then had the effect of not only silencing critical groups but also moderating sharia to become more open and inclusive. More importantly, the local-branded sharia became a common ground for the various Islamist groups to coalesce and, indeed, suppress vigilante action to renounce violent threat, at the very least, and served to lessen the divides between them. In this regard, the so-called sharia was like âkilling two birds with one stoneâ that on one side was a form of moderation to the critical groups but, on the other, was designed to be a common ground for various Islamist groups to coalesce. [Berdasarkan penelitian di Kabupaten Cianjur, Jawa Barat, shariatisasi di Indonesia telah mengambil bentuk lokal dengan mengganti istilah âshariahâ dengan âakhlaq al-karimahâ. Hal ini tidak hanya membungkam kelompok kritis, tetapi juga memoderasi syariah menjadi lebih terbuka dan inklusif. Terpenting adalah lokalisasi syariah menjadi landasan bersama bagi berbagai kelompok Islam untuk berkoalisi, dan alih â alih menekan aksi massa yang bisa menimbulkan kekerasan, dan yang menimbulkan perpecahan diantara mereka. Dalam hal ini, perumpamaannya seperti âsekali lempar, dua burung terjatuhâ, yang mana satu sisi merupakan bentuk moderasi kelompok kritis, satu sisi yang lain menjadi pondasi bersama koalisi berbagai kelompok Islam.]